California Democratic Platform 1964 (1964)
The document is the 1964 California Democratic Party Platform, adopted at the Democratic State Convention in Sacramento. It outlines the party's support for Governor Pat Brown and President Lyndon B. Johnson and details policy positions on agriculture, labor rights, economic growth, consumer protection, taxation, veterans' services, welfare, public health, education, housing, civil rights, and water resource development.